Surgery for Pulmonary Metastases: Long-Term Survival in 281 Patients - Dudek, Wojciech; Schreiner, Waldemar; Haj Khalaf, Mohamed; Sirbu, Horia (The Thoracic and Cardiovascular Surgeon, 2021)
Background Despite weak evidence, pulmonary metastasectomy (PM) is widely performed with intent to improve patient survival. Our single-institution analysis aims to evaluate outcomes and to identify factors influencing survival of patients undergoing PM for metastases from wide range of primary tumors.Materials and Methods All patients undergoing curative-intent PM between 2008 and 2018 were retrospectively analyzed. The impact of factors related to primary tumor, metastases, and associated therapy on overall survival (OS) was evaluated using univariable and multivariable Cox proportional hazard models. Cutoff values of continuous variables were determined by a receiver operating characteristic analysis.Results In this study, 281 patients (178 male, median age 61 years) underwent PM. Two (0.7%) perioperative deaths and 23 (8.2%) major complications occurred. Median interval between the treatment of primary tumor and PM was 21 months. Median size of largest metastasis was 1.4 cm. After the median follow-up of 29 months, 134 patients (47.7%) had died. Five-year OS rate after first PM was 47.1%. Complete resection was achieved in 274 (97.5%) patients. Multivariable analysis identified genitourinary origin (hazard ratio [HR]: 0.30, 95% confidence interval [CI]: 0.15–0.60, p = 0.0008) as independent positive survival prognosticator; incomplete resection (HR: 3.53, 95% CI: 1.40–8.91, p = 0.0077) and age at PM of ≥66 years (HR: 1.97, 95% CI: 1.36–2.85, p = 0.0003) were negative prognosticators.Conclusion The use of PM as a part of multimodal treatment is in selected population justified. Our analysis identified age, primary tumor origin, and completeness of resection as independent survival prognosticators.
Keywords: lung metastases; prognosis; metastasectomy